2017
DOI: 10.1177/1744806917715173
|View full text |Cite
|
Sign up to set email alerts
|

Molecular, cellular, and behavioral changes associated with pathological pain signaling occur after dental pulp injury

Abstract: Persistent pain can occur after routine dental treatments in which the dental pulp is injured. To better understand pain chronicity after pulp injury, we assessed whether dental pulp injury in mice causes changes to the sensory nervous system associated with pathological pain. In some experiments, we compared findings after dental pulp injury to a model of orofacial neuropathic pain, in which the mental nerve is injured. After unilateral dental pulp injury, we observed increased expression of activating transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 68 publications
1
26
0
1
Order By: Relevance
“…The association of reporting neuropathic pain descriptors and observing pain on percussion suggests that there could be a neuropathic component of painful toothache. Our group previously demonstrated in mice that markers of nerve injury are upregulated after pulp injury (Lee et al, ). As 3%–10% of patients experience persistent pain after dental interventions such as root canal treatments, these findings raise the question whether the neuropathic injury might occur before the dental intervention even takes place (Nixdorf et al, ; Polycarpou, Ng, Canavan, Moles, & Gulabivala, ; Vena et al, ).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The association of reporting neuropathic pain descriptors and observing pain on percussion suggests that there could be a neuropathic component of painful toothache. Our group previously demonstrated in mice that markers of nerve injury are upregulated after pulp injury (Lee et al, ). As 3%–10% of patients experience persistent pain after dental interventions such as root canal treatments, these findings raise the question whether the neuropathic injury might occur before the dental intervention even takes place (Nixdorf et al, ; Polycarpou, Ng, Canavan, Moles, & Gulabivala, ; Vena et al, ).…”
Section: Discussionmentioning
confidence: 92%
“…More recently, pre‐clinical and clinical studies determined that percussion hypersensitivity may identify mechanical allodynia due to central sensitization, regardless of the pulp status as vital or not (Latremoliere & Woolf, ; Owatz et al, ; Pigg, Nixdorf, Nguyen, Law, & National Dental Practice‐Based Research Network Collaborative Group, ). Studies using animal models of pulpitis have shown that even when inflammation is confined to the fully vital pulp, neuroplasticity is observed in the nucleus caudalis including upregulation of p38 MAPK, increased expression of markers of microglia and astrocytes and central sensitization (Lee et al, ; Worsley, Allen, Billinton, King, & Boissonade, ; Xie et al, ). These changes in the central nervous system can contribute to mechanical hypersensitivity and allodynia, which is observed as painful percussion on a clinical exam.…”
Section: Discussionmentioning
confidence: 99%
“…Although the model presented here is an inflammatory pain model, the DPI model has clear similarities to the orofacial mental nerve neuropathic (MNI) pain model, as we have previously described 11 . For example, we previously showed that both DPI and MNI induce trigeminal neuron expression of the injury gene activating transcription factor 3 (ATF3) and one week after both of these injuries we observed hypersensitivity to mechanical hind paw stimulation, indicating a central sensitization phenotype 11 . Although the studies here demonstrate that our methods are useful for assessing inflammatory pain in the tooth pulp, future studies are needed to determine if these methods will be useful in measuring pain in neuropathic pain models in the trigeminal region.…”
Section: Discussionmentioning
confidence: 98%
“…We have recently improved on this method by incorporating high-speed videography, statistical modeling, and machine learning to more objectively assess the mouse pain state following hind paw stimulation 10 . VFHs can also be applied to the face, but this presents more challenges because the animal's attention is more engaged with the stimulus, as we have previously experienced 11 . However, recent elegant work in freely behaving mice used both VFH stimulation of the whisker pad and optogenetic activation of trigeminal nociceptors to uncover a craniofacial neural circuit for pain 12 , demonstrating feasibility of the VFH approach for the study of oral pain.…”
mentioning
confidence: 99%
“…We have recently improved on this method by incorporating high-speed videography, statistical modeling, and machine learning to more objectively assess the mouse pain state following hind paw stimulation 10 . VFHs can also be applied to the face, but this presents more challenges because the animal’s attention is more engaged with the stimulus, as we have previously experienced 11 . However, recent elegant work in freely behaving mice used both VFH stimulation of the whisker pad and optogenetic activation of trigeminal nociceptors to uncover a craniofacial neural circuit for pain 12 , so it is not impossible.…”
Section: Introductionmentioning
confidence: 99%